FINANCIAL AND ECONOMIC BASIS AND PRINCIPLES OF ORGANIZING INTER-BUDGET RELATIONS - Ko‘makova Aziza Zayniddin qizi (Scholar Express Journals, 2023)
This article examines and studies the theoretical foundations of the formation and strengthening of local budget revenues in the context of ensuring macroeconomic stability. The current state of formation of local budget revenues and its composition is analyzed. It is based on the need to increase their income base in order to reduce the level of subsidies in local budgets. A system of practical recommendations of macroeconomic and financial description has been developed to strengthen the revenue base of local budgets.
Keywords: budget; local budget; subsidy; capital